Research on Factors Influencing the Effectiveness of Social Network Recruitment in Chinese Companies - huang, hao (2020)
The purpose of this study is to discuss and analyse the factors that influence the effect of social network recruitment in the context of more and more enterprises using the social network for recruitment from the perspective of employers. The participants were 220 employees from China. The data were collected by means of the questionnaire survey. A total of 200 valid questionnaires have been received. The results show that, from the perspective of corporate recruiters, there are seven factors that have a positive and significant impact on the effectiveness of corporate social network recruitment at the enterprise level and social network platform level. Through the research, it is found that the company can recruit better employees by establishing a right brand image, selecting professional skills, high quality and professional recruitment activities, and selecting a recruitment social network platform designed to meet with new forms according to the job characteristics. Actively encourage employees to participate in the forwarding of recruitment information and expand the coverage of the information is also useful in social network recruitment.